Jurnal Analyzing Therapy for Children with Special Needs: Slow Learners and Mentally Impaired Using the Literature Review Method: Menganalisis Terapi Anak Berkebutuhan Khusus: Slow Learner dan Tunagrahita dengan Metode Tinjauan Pustaka - Nadia Chairani Lia (Asesment : Journal Of Counseling Guidance, 2023)
Children with physical and motor disorders are people with forms of abnormalities or disorders in the muscle, bone and joint systems which can result in impaired coordination, communication, adaptation, mobilization and impaired development of personal integrity. This research aims to find out the basic concepts and appropriate stages of therapy for children with special needs with intellectual, physical, motor, mental retardation and slow learners. With this research, the education system of inclusive schools for children with special needs is given more attention by implementing but which is appropriate for children with special needs. intellectual disabilities, physical motor skills, mental retardation, and slow learners. This research method is Literature Review or literature review. Method of searching for articles in research journal databases and searching via the internet. This Literature Review was synthesized using a narrative method. The data used in this research is secondary data. Based on search results on Google Scholar with the keywords children with special needs, physical motor barriers, intellectual barriers and slow learners, researchers found 1,180 journals that matched these keywords. One way to overcome the dysfunction that occurs in a mentally retarded person so that the body organs of a mentally retarded child function optimally is by carrying out various types of therapy.